Congenital Heart Disease and Impacts on Child Development - Mari,Mariana Alievi (2016)
Abstract Objective: To evaluate the child development and evaluate a possible association with the commitment by biopsychosocial factors of children with and without congenital heart disease. Methods: Observational study of case-control with three groups: Group 1 - children with congenital heart disease without surgical correction; Group 2 - children with congenital heart disease who underwent surgery; and Group 3 - healthy children. Children were assessed by socio-demographic and clinical questionnaire and the Denver II Screening Test. Results: One hundred and twenty eight children were evaluated, 29 in Group 1, 43 in Group 2 and 56 in Group 3. Of the total, 51.56% are girls and ages ranged from two months to six years (median 24.5 months). Regarding the Denver II, the children with heart disease had more "suspicious" and "suspect/abnormal" ratings and in the group of healthy children 53.6% were considered with "normal" development (P≤0.0001). The biopsychosocial variables that were related to a possible developmental delay were gender (P=0.042), child's age (P=0.001) and income per capita (P=0.019). Conclusion: The results suggest that children with congenital heart disease are likely to have a developmental delay with significant difference between children who have undergone surgery and those awaiting surgery under clinical follow-up.